The importance of using techniques, methods, and tools, both printed and digital, for effective translation. - Calderón Torres, Andrea Beatriz; Quintanilla Rivas, Raúl Antonio; Villalobos Santamaria, Andrea Elena (Universidad de El Salvador. Facultad de Ciencias y Humanidades., 2024)
Disponible en soporte impreso.